Ginkgo biloba leaf extract EGb 761® as a paragon of the product by process concept - Kulić, Žarko; Lehner, Martin D.; Dietz, Gunnar P. H. (Frontiers in Pharmacology, 2022)
It is an often-neglected fact that extracts derived from the very same plant can differ significantly in their phytochemical composition, and thus also in their pharmacokinetic and pharmacodynamic properties which are the basis for their clinical efficacy and safety. The Ginkgo biloba special extract EGb 761® is one of the best-studied plant extracts in the world. In the present review, using that extract as a paradigm, we describe insights how climate, the harvest region, processing of the plant material, the drying process, the extraction solvents, and the details of the subsequent process steps substantially impact the quality and uniformity of the final extract. We highlight the importance of regulating active constituent levels and consistent reduction of undesired substances in herbal extracts. This is accomplished by a controlled production process and corresponding analytical specifications. In conclusion, since extracts derived from the same plant can have very different phytochemical compositions, results from pharmacological, toxicological and clinical studies gained with one specific extract cannot be extrapolated to other extracts that were generated using different production processes. We propose that the heterogenous nature of extracts should be meticulously considered when evaluating the efficacy and safety of plant-derived remedies.